Isotopic characteristics of Crimean collection wines - L. A. Oganesyants; A. L. Panasyuk; E. I. Kuzmina; D. A. Sviridov; V. V. Likhovskoy; V. A. Zagoruiko; N. A. Shmigelskaya (Пищевые системы)
Collection wines are a special category of winemaking products, which acquire their unique characteristics during aging. One of the first wine collections in Russia was created in 1833–1835 in the Magarach state establishment, which is now the AllRussian National Research Institute of Viticulture and Winemaking “Magarach”. The large part of the Magarach collection consists of strong wines. These wines were produced by introducing alcohol of different nature (grape, grain, molasses), which was conditioned by the requirements of the legislation that was in force at the moment of production. It was interesting to find out the nature of alcohol that was used for wine alcoholization in the preceding decades. To this end, the method of isotope mass spectrometry was used. In addition, it was necessary to establish whether the values of isotopic characteristics of carbon, oxygen and hydrogen of ethanol of grape origin have changed over the last decades. The objects of the research were 15 samples of Crimean collection wines, one of which was dry wine of the 1982 harvest and 14 strong wines were from harvests of the last century with the oldest wine made from grape of the 1937 harvest. The composition of the stable carbon isotopes of ethanol in the samples was determined using the analytical complex Delta V Advantage. It has been found that the dry wine of 1982 harvest was produced without adding alcohol. Although the age of the drink is more than 40 years, the values of the isotopic characteristics of the elements of ethanol are typical for the modern products made exclusively from grape. Thus, the isotopic characteristics of carbon, oxygen and hydrogen of sugars of grape berry did not change significantly over the studied period. When analyzing strong wines, it has been established that the values of the isotopic characteristics of carbon were in a range of –27.23‰ to –24.13‰ (except one sample with a value of –15.49‰); the corresponding values for oxygen were from 7.21‰ to 17.09‰ and for hydrogen from –270‰ to –216‰. Therefore, for most studied samples, the obtained values of isotopic characteristics of the elements of ethanol were typical precisely for the mixture of grape and grain alcohols.